Transformasi Ekonomi Digital di Indonesia: Peluang,Tantangan, dan Dampak nya terhadap perekonomian - Novariani Indri Utami; Feri Setyowibowo; Kresna Bayu Sangka (EBISMAN eBisnis Manajemen, 2025)
The transformation of the digital economy has become a significant phenomenon in Indonesia’s economic development, driven by rapid advances in information and communication technology. The digital economy is viewed as a strategic instrument to accelerate economic growth, enhance financial inclusion, and strengthen the competitiveness of business actors, particularly micro, small, and medium enterprises (MSMEs). This study aims to analyze the transformation of the digital economy in Indonesia by examining its opportunities, challenges, and impacts on the national economy. The research adopts a qualitative approach using a literature review method, drawing on relevant national and international academic journals. Data analysis is conducted through a descriptive-qualitative approach by linking empirical findings with the theoretical frameworks of innovation economics and endogenous growth theory. The findings indicate that the digital economy offers substantial opportunities to improve efficiency, productivity, financial inclusion, and the creation of new digital-based employment. However, the transformation also faces major challenges, including the digital divide, limited human resource capacity, and issues related to regulation and data security. The implications of this study highlight the importance of strengthening digital infrastructure, enhancing digital literacy and skills, and developing adaptive governance frameworks to ensure that the digital economy contributes optimally and sustainably to Indonesia’s economic development.